Jogos em aparelhos tecnológicos vivenciados por crianças : processos educativos envolvidos - Morais, Vinícius Barbosa de (2017)
With the notorious globalization of technological products and the great facility for their acquisition nowadays, children are entering this "technological world" earlier and earlier, mainly to experience virtual games. There is a certain fear of adults regarding the use that children make of their technological devices, mainly related to the social dimension, as something that disrupts their interpersonal relationships, however there are also those who value the games in these devices as a fundamental part of the culture of today's children. This is mainly due to the fact that the child is constructing a ludic culture during the life that originates from their social interactions, appropriating this culture also in the use of their technological devices. That way, the contact with this type of game during their interpersonal relations with their peers can even favor spaces for educational processes appear. From this scenario, this study aims to identify the relationships established by children of a sixth grade elementary school when they are playing in their technological devices and how they organize their games. For the data collection, participant observations were made in recreation and physical education classes, dialoguing and experiencing games in technological devices at these moments. Observations were recorded in field diaries. Another collection technique was the thematic conversation with children during classes in Physical Education. For data analysis, all the material obtained in the research was analyzed based on the theoretical and methodological assumptions of content analysis. The results evidenced that the subjects of this research, while playing in their technological devices, appropriate these as a means to interact with their peers, to observe and learn other things, in order to better coexist with the other children in this technological world in which they are inserted. It was also noticed that these children, almost at all times, wanted to share knowledge, exchange information, meet new games, reflect on their relationships with this type of game and with friends, finally, explore this world of virtual games and all its possibilities in contact with their peers. We conclude that for the subjects of this research the games in technological devices are more like a way of playing and, therefore, they feel more and more attracted to them, yet they are not open to the other possibilities of play that the time of the childhood offers, which contributes to a widening of the possibilities of fun in their life context.